Association Between Lipid Profile ,BMI , and Some Pituitary Hormones Abnormalities In Sera of Iraqi Infertile Females - Mahmood, A. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study , the clinical impact of interaction between gonadotrophin hormones (luteinzing hormone, LH, and follicle stimulating hormone ,FSH ) and prolactin PRL in serum of seventeen Iraqi infertile female with the lipid profile . In addition to control group involving age matched fertile females . Immunoradiometric assay ( IRMA ) technique for the determination of (LH , FSH and PRL) was utilized. The lipid profile i.e. total cholesterol ( Tc ) , triglycerides (TG) , and high density lipoprotein – Cholestrol ( HDLc ) ,were evaluated by using colorimetric method , while low density lipoprotein cholesterol ( LDLc ) and very low density lipoprotein – cholesterol ( VLDLc ) , were evaluated by using a mathematical formulas. The body mass index ( BMI ) was calculated as weight ( Kg) / height ( m² ). The results revealed that only( 20%) of infertile female with abnormal hormonal levels are obese , while (40% )of them were overweight . Only (TG ) in sera of infertile female showed a significant increase than that of control group. On the other hand no significant differences in (Tc) , (HDLc) were noticed in sera of groups under consideration . A conclusion could be obtained from the above data , that (BMI )or obesity is not associated with infertility always.